Stress distribution evaluation of complete denture with soft denture liners in knife-edge alveolar ridge using finite element analysis - Tiroi Paulina; Ariyani; Ismet Danial Nasution (Indonesian Journal of Prosthodontic, 2023)
Edentulous induces the function of the stomatognathic system particularly masticatory performance. The conse-quence that occurs in complete edentulous is the resorption of residual ridge and can alter the morphology of al-veolar bone gradually from well-rounded to knife-edge ridge form. Excessive occlusal load absorbed by the knife-edge alveolar ridge when the denture is exposed to masticatory loads enhances ridge resorption and more complex treatments are needed in manufacturing complete dentures (CD). Soft denture liners (SDL) overcome CD problems with knife-edge ridges by utilizing the cushioning effect by distributing the load evenly to the alveolar ridge. The most popular method used today to evaluate the stress distribution at the alveolar ridge is finite element analysis (FEA) because it presents information in both qualitative and quantitative forms. This study is aimed to evaluate the differ-ences in stress distribution received by knife-edge ridges in CD with SDL. Denture base applied with acrylic soft den-ture liner (ASDL) and silicone soft denture liner (SSDL). It is concluded that ASDL provides a better stress distribution than SSDL because of its viscoelasticity, while SSDL is superior in terms of durability.